Pengaruh Corporate Governance Perception Index (CGPI) dan Opini Audit terhadap Harga Saham (Studi Empiris pada Perusahaan yang Terdaftar di The Indonesian Institute for Corporate Governance Tahun 2009-2013) - Sunardi -; Holiawati - (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2016)
This research aimed to examine the effect of Corporate Governance Perception Index (CGPI) and Audit Opinion on Stock Price on listed companies in The Indonesian Institute for Corporate Governance (IICG) years 2009-2013. In this study, there are two independent variables, Corporate Governance Perception Index (CGPI) and Audit Opinion, and one dependent variable is the Stock Price.  The sampling method used in this research is purposive sampling method. The number of populations found in this study were fifty nine companies with a number of sample as much as nine companies that meet the criteria. The data used was the secondary data which was obtained from www.idx.co.id, www.iicg.org, and www.swa.co.id with forty five observations data. The analysis of the research used the multiple linear regression, and then to test in multiple linear regression studies using software the Statistical Product and Service Solutions (SPSS) version 22 for Windows using t test (partial) and F test (simultaneous).  Based on the results of study showed that; partially CGPI (X1) doesn’t have significant effect on Stock Price, partially Audit Opinion (X2) significant effect on Stock Price (Y), and simultaneously CGPI (X1) and Audit Opinion (X2) significant effect on Stock Price (Y).